2022
DOI: 10.1186/s12958-021-00883-1
|View full text |Cite
|
Sign up to set email alerts
|

Human plasma pregnancy-associated miRNAs and their temporal variation within the first trimester of pregnancy

Abstract: Background During pregnancy, maternal metabolism undergoes substantial changes to support the developing fetus. Such changes are finely regulated by different mechanisms carried out by effectors such as microRNAs (miRNAs). These small non-coding RNAs regulate numerous biological functions, mostly through post-transcriptional repression of gene expression. miRNAs are also secreted in circulation by numerous organs, such as the placenta. However, the complete plasmatic microtranscriptome of pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…To ensure comparability and standardization of data between platforms, 12 samples were extracted twice and sequenced on both platforms. These samples showed high correlation in miRNA levels (ie, Pearson correlation coefficient ≥0.94) 19 and confirmed that our sequencing approach is accurate.…”
Section: Methodssupporting
confidence: 76%
See 4 more Smart Citations
“…To ensure comparability and standardization of data between platforms, 12 samples were extracted twice and sequenced on both platforms. These samples showed high correlation in miRNA levels (ie, Pearson correlation coefficient ≥0.94) 19 and confirmed that our sequencing approach is accurate.…”
Section: Methodssupporting
confidence: 76%
“…C19MC is exclusive to primates, maternally imprinted (paternally expressed) and encodes 46 miRNA genes producing 58 mature miRNAs. 11 In a previous study from our group, 19 we have identified miRNAs upregulated and downregulated in pregnancy and varying in concentration between 4th and 16th week of pregnancy. Out of the 15 miRNAs we have identified from C19MC and being associated with IS, 7 miRNAs were upregulated in pregnancy and 11 miRNAs (5 were common) were showing increasing levels as the pregnancy progresses from 4th to 16th week.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations